2019
DOI: 10.1111/tger.12084
|View full text |Cite
|
Sign up to set email alerts
|

Using Flipped Learning to Facilitate Cross‐Cultural Critical Thinking in the L2 Classroom

Abstract: Flipped learning is robust instruction made possible by leveraging technology to create fertile spaces for teaching and learning." (Marshall, 2015, slide 7) 53 52 UP 52.1 (Spring 2019)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…Regarding the positive effect of FC and authentic audio-visual materials on the enhancement of intercultural competence in general and intercultural sensitivity and effectiveness in particular, the results of this study confirm the findings of Desai et al ( 2018 ), Zhang ( 2020 ), and Jensen ( 2019 ). Consequently, the development of both ICS and ICE in this study following the models of Byram ( 1997 ), Deardorff ( 2006 ), and Bennett ( 2004 ) reveals that intercultural development through culture-simulated audio-visual authentic material accompanied by scaffolding discussions is plausible in an EFL context where direct exposure to the foreign culture seems improbable (Namaziandost et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the positive effect of FC and authentic audio-visual materials on the enhancement of intercultural competence in general and intercultural sensitivity and effectiveness in particular, the results of this study confirm the findings of Desai et al ( 2018 ), Zhang ( 2020 ), and Jensen ( 2019 ). Consequently, the development of both ICS and ICE in this study following the models of Byram ( 1997 ), Deardorff ( 2006 ), and Bennett ( 2004 ) reveals that intercultural development through culture-simulated audio-visual authentic material accompanied by scaffolding discussions is plausible in an EFL context where direct exposure to the foreign culture seems improbable (Namaziandost et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“…Zhang ( 2020 ) explored the development of Chinese learners' intercultural competence through authentic video and found out that their intercultural competence expanded, and students became more culture-tolerant, empathetic, and sensitive. In another study, Jensen ( 2019 ) examined the effect of FC on L2 students' cross-cultural critical thinking and found that students' cross-cultural critical awareness improved.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The articles reviewed were the results of research conducted in junior high school [27], [28], senior high school [13], [29], [30], and higher education [8], [15], [31]- [39] levels in different countries (Hong Kong, South Africa, USA, Malaysia, Taiwan, England, Iran, Palestine, Vietnam, Indonesia, and Philippines). The results of the review are presented in Table 1 (the order of articles is based on the year of publication) and described based on the research questions, as follows:…”
Section: Resultsmentioning
confidence: 99%
“…The models supported an effective, interesting, and the student-centered learning process. [39] Conducted at a university in Carolina, United States, especially in a third-semester German language course (N=12). Aim: To propose using the FC approach to promote critical cultural awareness by developing cross-cultural CT skills.…”
Section: A Student Learning Activities and Technology Used In Fc To Develop Ctmentioning
confidence: 99%
“…As the materials related to knowledge had been given to students before the class, thus students and teachers could spend more of the class time for activities and tasks in more details (Gürsoy & Orhan Göksün, 2020). In addition, FL has assisted students to have positive attitude towards the use of technology for language learning (Webb & Doman, 2020), FL encourages Cross-Cultural Critical Thinking in the L2 classroom (Jensen, 2019), prevents demotivation in writing class (Wu et al, 2020), boosts learners' autonomy on their learning (Tsai, 2019), and facilitates students' needs in time of crisis caused by natural disaster such as experienced by students of Indonesian EFL writing class during the post-earthquake in Mataram (Husnawadi, 2021).…”
Section: Introductionmentioning
confidence: 99%